2016
DOI: 10.1158/1078-0432.ccr-15-0905
|View full text |Cite
|
Sign up to set email alerts
|

New Strategies in Myeloproliferative Neoplasms: The Evolving Genetic and Therapeutic Landscape

Abstract: The classical BCR-ABL1-negative myeloproliferative neoplasms (MPNs) include essential thrombocythemia (ET), polycythemia vera (PV) and myelofibrosis (MF). While these clonal disorders share certain clinical and genetic features, MF in particular is distinct for its complex mutational landscape, severe disease phenotype and poor prognosis. The genetic complexity inherent to MF has made this disease extremely challenging to treat. Pharmacologic JAK inhibition has proven to be a transformative therapy in MPNs, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 128 publications
(121 reference statements)
0
11
0
Order By: Relevance
“…In recent years, targeted NGS panels have been used in oncology for early detection of tumor, risk stratification and prognosis, disease monitoring, and targeted therapy . Mutational analysis for patients with unexplained cytopenia is becoming common practice, especially in large academic medical centers .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, targeted NGS panels have been used in oncology for early detection of tumor, risk stratification and prognosis, disease monitoring, and targeted therapy . Mutational analysis for patients with unexplained cytopenia is becoming common practice, especially in large academic medical centers .…”
Section: Introductionmentioning
confidence: 99%
“…Other phase I trial (NCT02436135) investigated the combination of RUX with idelalisib, a PI3K delta inhibitor, as therapy for intermediate to high-risk PMF, post-PV MF, or post-ET MF with progressive or relapsed disease [127].…”
Section: Pcd Resistance In Myeloid Proliferation Exploited In Single mentioning
confidence: 99%
“…Due to the preclinically proved synergic effects of PI3K/AKT/mTOR inhibitors and JAK inhibitors, several clinical studies were initiated: PI3K inhibitor TGR-1202 in combination with RUX (NCT02493530), PI3K inhibitor buparlisib with RUX (NCT01730248), PI3K inhibitor INCB050465 and RUX (NCT02718300), and selective PI3Kδ inhibitor TGR-1202 and RUX (NCT02493530). Preliminary results of buparlisib and RUX phase 1b study indicated that this drug association was well tolerated, and ≥ 50% reduction in splenomegaly was observed in 70% of JAK-inhibitor naive patients and 54% of patients who did not previously respond to JAK2 inhibitor monotherapy [97,127].…”
Section: Pcd Resistance In Myeloid Proliferation Exploited In Single mentioning
confidence: 99%
“…25 Treatment reduces splenomegaly, itch and fatigue and improves survival but the newer agents now in phase 3 trials, such as momelotinib and pacritinib, may offer similar efficacy with a lower risk of myelosuppression (though they may have other adverse effects such as, in the case of momelotinib, peripheral neuropathy). 26 …”
Section: Myeloproliferative Disordersmentioning
confidence: 99%